2018
DOI: 10.1002/jmri.26178
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic features from pretreatment biparametric MRI predict prostate cancer biochemical recurrence: Preliminary findings

Abstract: 4 Technical Efficacy: Stage 5 J. Magn. Reson. Imaging 2018;48:1626-1636.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(73 citation statements)
references
References 35 publications
1
70
1
1
Order By: Relevance
“…When compared with traditional Cox regression analysis, the three ML algorithms had superior prediction performance. Tissue morphometric data , imaging radiomic features , and tissue genomic profiling were also used to predict patient outcomes. These studies showed that AI algorithms trained with clinicopathological data, imaging radiomic features and genomic profiling outperformed the prediction accuracy of D'Amico risk stratification, single clinicopathological features, or multiple discriminant analysis, a type of conventional multivariate statistics .…”
Section: Application Of Ai In Urologymentioning
confidence: 99%
“…When compared with traditional Cox regression analysis, the three ML algorithms had superior prediction performance. Tissue morphometric data , imaging radiomic features , and tissue genomic profiling were also used to predict patient outcomes. These studies showed that AI algorithms trained with clinicopathological data, imaging radiomic features and genomic profiling outperformed the prediction accuracy of D'Amico risk stratification, single clinicopathological features, or multiple discriminant analysis, a type of conventional multivariate statistics .…”
Section: Application Of Ai In Urologymentioning
confidence: 99%
“…For example, statistical descriptors can be particularly sensitive to the intensity of the image. Texture features of DWI, among other radiomic features, have already demonstrated some promise for PCa detection and management (e.g., Shiradkar et al and Algohary et al). However, a large variation in radiomics performance has been observed in multi‐institutional studies .…”
Section: Discussionmentioning
confidence: 99%
“…Aggressiveness of PCa is histologically determined by Gleason score that is classified into Gleason grade group (GGG) . Various radiomics and ML methods have already been developed for PCa detection and characterization (e.g., Shiradkar et al and Algohary et al). However, radiomics and ML methods have not been evaluated in terms of their repeatability, which contributes to reservations of making imaging applications that would use prostate MRI more extensively coupled with machine learning in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sequences can provide considerable advantages in presenting the different components of tumors. A radiomics model, which is based on a large number of imaging features, has been regarded as a powerful prognostic biomarker for cancer recurrence . Thio et al recently developed different machine‐learning models for predicting the 5‐year survival rates of CS patients; however, further validation is needed .…”
mentioning
confidence: 99%